2017
DOI: 10.1111/bdi.12466
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of correlations between DNA methylation, suicidal behavior and aging

Abstract: Objectives: Suicidal behavior (SB) is a major cause of mortality for patients diagnosed with bipolar disorder (BD). In this study, we investigated epigenetic differences in BD participants with and without a history of SB. Methods:We used suicidality scores constructed from Schedule for Clinical Assessments in Neuropsychiatry (SCAN) interview questions about suicidal thought and behavior to identify individuals from a BD cohort of n=452; participants with the most extreme high (H-SB, n=18) and most extreme low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…The third gene identified for EAs with gene-based association analysis was PGBD5 ; it maps 5 MB from “Nucleoporin 133” ( NUP133 ); the latter locus was epigenome-wide significant in a study using a quantitative suicidality score 37 . Although the authors of that study focused more on NUP133 , PGBD5 was discussed for its proximity to top findings and overlap with findings in panic-induced epigenetic H3K27me3 modifications in mice 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third gene identified for EAs with gene-based association analysis was PGBD5 ; it maps 5 MB from “Nucleoporin 133” ( NUP133 ); the latter locus was epigenome-wide significant in a study using a quantitative suicidality score 37 . Although the authors of that study focused more on NUP133 , PGBD5 was discussed for its proximity to top findings and overlap with findings in panic-induced epigenetic H3K27me3 modifications in mice 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we identified several associations in genes or associated pathways that have previously been implicated in suicide. Epigenetic modifications near PGBD5 and NUP133 have been associated with quantitative scores for suicidality 37 . Suicidal ideation state changes have been associated with the increased expression of PHLDB2 in independent studies in men 36 and women 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a possible role of modified expression of such genes as MPP4 (membrane palmitoylated protein 4), nucleoporin (NUP133), a member of the TRE2/ BuB2/CDC16 family of domains (TBC1D16), the alpha1 subunit of the gamma-aminobutyric acid receptor (GABRA1) in SB development. In particular, a total decrease in methylation in the 5′-UTR of the MPP4 gene and in intron 3 of the TBC1D16 gene together with increased methylation in exon 1 of the NUP133 gene was observed in patients with bipolar disorder and comorbid SB compared to the control group (Jeremian et al, 2017). In addition, hypermethylation of CpG islands in the promoter of the GABRA1 gene was associated with changes in mRNA expression of the DNA methyltransferase gene (DNMT) in the brain of individuals with completed suicide (Poulter et al, 2008).…”
Section: Changes In Dna Methylation and Histone Modificationmentioning
confidence: 93%
“…In a study researchers compared blood methylation profile between patients with bipolar disorder showing suicidal behaviour and patients who showed no such behaviour. They as well observed differential levels of methylation of multiple genome regions in patients with suicidal behaviour, identifying three potential candidate genes (Jeremian et al 2017). One of the biggest studies so far observed methylation levels in blood and a subset sample of prefrontal cortex in patients with major depressive disorder.…”
Section: Suicidal Behaviour and Genome-wide Dna Methylation Studiesmentioning
confidence: 99%